Analisis Resiko Produksi Resiko Harga dan Pendapatan Pada Usahatani Cabai Rawit di Desa Pakkabba Kecamatan Galesong Utara Kabupaten Takalar - Rahmatullah Hidayat; Mohammad Natsir; Ardi Rumallang (Jurnal Agribis, 2022)
This study aims to determine the analysis of production risk, price risk and income on cayenne pepper farming in Pakkabba Village, North Galesong District, Takalar Regency. The population of cayenne pepper farmers in Pakkabba Village, North Galesong District, Takalar Regency is 25 people. The technique of determining the sample is carried out by the Census method. Data collection is carried out by interviews. The results showed that the product risk analysis was 0.38 and the price risk obtained was 0.36. This means that the production risk and price risk in cayenne pepper farming in Pakkabba village are classified as moderate. Meanwhile, the income of cayenne pepper farmers in Pakkabba Village, North Galesong District, Takalar Regency is Rp. 26,331,915.